Peran Filsafat Pendidikan sebagai Fondasi Transformasi Kesehatan - Pauzi, Iswari; Sarjan, Muhammad; Muliadi, Agus; Azizi, Asrorul; Hamidi, Hamidi; Yamin, Muhammad; Muttaqin, Muh. Zaini Hasanul; Ardiansyah, Bakhtiar; Rahmatiah, Rindu; Sudirman, Sudirman; Rasyidi, Mulia; Khery, Yusran (Biocaster : Jurnal Kajian Biologi, 2022)
The purpose of educational philosophy is to inspire how to organize an ideal learning process. Educational theory aims to generate ideas about educational policies and principles based on educational philosophy. Philosophy of education is a philosophical  that studies the nature of implementation and tries to answer questions about educational policy, human resources, curriculum and learning theory and other aspects of education that start with questions about what, why and how, which is the main basis of philosophy. In facing the era of globalization and digitalization, the Ministry of Health has made policies to implement Health Transformation, including; Transformation of human resources by establishing new study programs, transformation of health service facilities and infrastructure, transformation of health services and transformation of new communicable diseases. From the results of this study, philosophy has an important role in supporting the transformation of health.